[Edge of Lava Flow and Houses in Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of the edge of a lava flow and houses along Heimaey. A round, cloud covered, brown mountain sits in the far distance, lava rock surrounding it and wrapping around the town to the left. White buildings with white, red, and green roofs sit in a cluster to the right. A single, red and yellow building with a green roof sits in the bottom right corner of the photograph, a laundry line hanging off of it. White flowers dot along the outside of the buildings.